THE ROLE OF TRUST IN MEDIATING THE INFLUENCE OF STRATEGIES ON MUZAKKI AWARENESS AT LAZISMU BANJARMASIN - Muzahid Akbar Hayat; Decky C. Kananto Lihu; Parihin (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the influence of communication strategies on the awareness of muzakki with muzakki trust as a mediating variable at LAZISMU Banjarmasin City. The study used a quantitative approach with a survey method. The study population was muzakki who had distributed zakat through LAZISMU Banjarmasin City, with a sample of 150 respondents determined using a purposive sampling technique. Data were collected through a questionnaire with a five-level Likert scale and analyzed using Structural Equation Modeling based on Partial Least Square (SEM-PLS). The results showed that communication strategies had a positive and significant effect on muzakki awareness and muzakki trust. In addition, muzakki trust also had a positive and significant effect on muzakki awareness. The results of the mediation test showed that muzakki trust was able to partially mediate the influence of communication strategies on muzakki awareness. These findings indicate that effective, transparent, and credible communication strategies play an important role in building muzakki trust and increasing awareness in paying zakat through official zakat institutions.